Flow and entrainment characteristics of density stratified liquids in a slotted compartment induced by a submerged flow stream - Chen, Charng Ning. (2008)
This project investigates the entrainment characteristics and feedback mechanisms in mixing layer oscillations induced by a flow beneath a rectangular compartment. An approximate unfied equation was derived for estimating the mixing rates across a density interface in rectangular and circular tanks with partially open bottoms, induced by a submerged flow stream below tanks.